DATA WAREHOUSE PADA E-LEARNING - Imam Husni Al Amin (Jurnal Ilmiah Dinamika Teknik, 2010)
e-Learning become a undoubtedly at college of this scat. This matter because e-learning can water down to access a student in have interaction to with its campus. Besides, e-learning will improve college swing days. To manage data bases of e-learning, will be more be valuable if applied by depository pattern with data of warehouse, because besides can accommodate data which is its volume very big, data of warehouse also can become tools to analyze wanted data (OLAP for example) and to take decision accurately and quickly. This article represent literature overview about data and e-learning of warehouse and also will try to see possibility use data of warehouse at e-learning.   Keywords: e-learning, data warehouse, repository